MicroRNA-365a-3p inhibits c-Rel-mediated NF-[kappa] B signaling and the progression of pancreatic cancer - Yin, Libo; Xiao, Xi; Georgikou, Christina; Yin, Yefeng; Liu, Li; Karakhanova, Svetlana; Luo, Yiqiao; Gladkich, Jury; Fellenberg, Jörg; Sticht, Carsten; Gretz, Norbert; Gross, Wolfgang; et al. (Cancer letters, 2019)
NF-κB contributes to the aggressiveness of pancreatic ductal adenocarcinoma (PDA), which is counteracted by the bioactive agent sulforaphane. We investigated sulforaphane-induced microRNA signaling and its influence on progression features. Using established cell lines, microRNA and gene arrays, we predicted miR-365a as the top candidate for the sulforaphane-induced inhibition of the NF-κB subunit c-Rel. The lipofection of miR-365a-3p mimics inhibited the luciferase activity of a c-Rel 3′-UTR construct, as well as c-Rel expression, NF-κB activity, and tumor viability, migration, and clonogenicity, whereas apoptosis was induced. In vivo, miR-365a-3p reduced the volume of tumor xenografts and the expression of progression markers. In a tissue array, the expression of miR-365a-3p was absent in almost all 91 malignant tissues but not in 5 normal tissues, thus confirming the previous results. Our observations suggest that sulforaphane-induced miR-365a-3p expression inhibits NF-κB activity by downregulating c-Rel, which prevents the progression of PDA.